When food becomes a drug: nonanabolic nutritional supplement use in athletes - Schwenk, T. L.; Costley, C. D. (The American Journal of Sports Medicine, 2002)
The use of nonanabolic nutritional supplements for the sake of improving athletic performance is common, and the types of supplements used can have significant implications for the medical care of athletes. This review will address the most common and most controversial nonanabolic nutritional supplements, including recommendations regarding their use. Many supplements are marketed and promoted based on various theoretical benefits, often derived from limited animal studies, without any basis for recommending their human use. Physicians are trained to not recommend a nutritional supplement unless it is known to be effective, whereas athletes are oriented toward trying any supplement or ergogenic aid as long as it is safe, with the hope that it may be effective. The built-in error in most study designs is larger than the difference between winning and not qualifying at elite levels of competition, such that research may not always answer the questions raised by athletes. An honest discussion of the limitations of most supplements, and acknowledgment that some supplements may work some of the time in some athletes, may lead the physician to be more credible and useful to athletes in providing medical care and guidance that support their desire to improve their performance.